Advances in antimicrobial techniques to reduce postharvest loss of fresh fruit by microbial reduction - Shiv Shankar; Amar K. Mohanty; Jennifer R. DeEll; Kathryn Carter; Ruben Lenz; Manjusri Misra (npj Sustainable Agriculture)
Abstract This review will provide new ideas for preserving fruits and decreasing fruit waste. This review outlines and evaluates research concerning postharvest fruit preservation employing antimicrobial strategies, which involve the integration of biological control alongside physical or chemical methods. The concurrent deployment of two or three of these techniques, particularly biological approaches, has demonstrated enhanced and synergistic antimicrobial outcomes in practical scenarios.